Potentiometric test strip - Dumschat, Christa; Borchardt, Michael; Diekmann, Christoph; Cammann, Karl; Knoll, Meinhard (Sensors and actuators. B, Chemical, 1995)
A potentiometric test strip has been developed. It consists of an indicator electrode and a reference electrode. Both electrodes are prepared on filter paper as a microfibre matrix, encapsulated by the use of heat-sealing film and separated by an insulating plastic film or held at a distance during measurement. The reference electrode is a redox electrode. For the preparation of the ion-selective electrode a standard ion-selective PVC-matrix membrane cocktail is deposited in the microfibre matrix. Potassium- and sodium-sensitive test strips have been prepared and characterized. The electrochemical response of the potentiometric test strips is close to that of macro ion-sensitive electrodes using the same ion-selective membrane material. It should be possible to produce the test strips by mass-production technologies. So in future they may offer a new possibility for a more precise low-cost on-site determination of ions.